Students Satisfactory Indexs of Pascasarjana Services of Universitas Ahmad Dahlan - Abdul Choliq Hidayat; Agus Siswanto (Forum Inovasi Bisnis dan Manajemen, 2019)
The research aim was to calculate Students Satisfactory Indexs of Pascasarjana Study Programs Services Of Universitas Ahmad Dahlan who has 12 (twelve) programs,. It has at least 850 students in 2018. Pascasarjana needs some feedback in order to increase their quality of students service satisfactory as high as possible to reach optimum level, and fulfill qualification of succeed its business. This research wanted to measure the up dated customer service satisfactory and gave feedback to Universitas Ahmad Dahlan for their continuous improvement program. The research method used quantitative approach to primary data of customer questioneer and scondary data of Pascasarjana Universitas Ahmad Dahlan. The questioneers had distributed to student that has one year full study, by proporsional random sampling to 11 of 12 study programs, 10 examplar each study program, totally about 110 examplars, returned back about 110 examplars (100%), and than the data have been calculated by SPSS method version 10.0. The result of research was students satisfactory indexs of the services of Pascasarjana Study Programs reached good and significance level at all study programs, as the index, at point 4.307 root mean at 1 until 5 at Likert scale. They favored empathy dimension at point 4.389, and than assurance (4.347),tangible (4.331), responsiveness (4.295), and reliability (4.185). To be adviced that all of study programs must increase giving their services until reach the highest level of all dimensions, that are: tangibles, responsiveness, reliability, emphaty, dan assurance. Both of hyphotesis have proven that all of five variables, together or partially were significantly and positively influenced toward Students Satisfactory of Pascasarjana Study Programs Services Of Universitas Ahmad Dahlan